Video-Assisted Thoracic Surgery (VATS) Lobectomy for Pathologic Stage I Non-Small Cell Lung Cancer: A Comparative Study with Thoracotomy Lobectomy - Park, Joon Suk (Korean Society for Thoracic and Cardiovascular Surgery, 2011)
BACKGROUND: Surgical treatment of stage I non-small cell lung cancer (NSCLC) can be performed either by thoracotomy or by employing video-assisted thoracic surgery (VATS). The aim of this study was to evaluate the feasibility of VATS lobectomy for pathologic stage I NSCLC. MATERIAL AND METHODS: Between December 2003 and December 2007, 529 patients with pathologic stage I NSCLC underwent lobectomies (373 thoracotomy, 156 VATS). Patients in both groups were selected after being matched by age, gender and pathologic stage using propensity score method, to create two comparable groups: thoracotomy and VATS groups, and the overall survival, recurrence-free survival, complication and length of hospitalization were compared between these two groups. RESULTS: After the patients were matched by age, gender and pathologic stage, 272 patients remained eligible for analysis, 136 in each group (mean age of 59.5 years; 70 men, 66 women; 80 stage IA, 56 stage IB). There was no statistical difference in other preoperative clinical characteristics between the two groups. No hospital mortality was observed in both groups. Overall 3-year survival rate was 97.4% in thoracotomy group and 96.6% in VATS groups (p=0.76). During the follow-up, 20 patients (14.7%) developed recurrence in thoracotomy group, including loco- regional recurrence in 7, distant metastasis in 13. In VATS group, 13 patients (9.6%) developed recurrence, including loco-regional recurrence in 4, distant metastasis in 9. Three-year recurrence-free survival rate was 81.8% in thoracotomy group and 85.3% in VATS groups (p=0.43). There was no significant difference in postoperative complications between thoracotomy and VATS groups (30 cases in 22 patients vs. 19 cases in 17 patients, p=0.65, odds ratio=1.19). The mean hospital stay of VATS group was 2 days shorter than that of thoracotomy group (8.8±6.5 days vs. 6.3±3.3 days, p<0.05). CONCLUSION: VATS lobectomy for pathologic stage I lung cancer is a feasible operation with shorter hospitalization, while surgical outcome is comparable to thoracotomy lobectomy.